Potential and Utilization Rate of Anchovy (Stolephorus sp) Landed at UPTD Fishery Port Region I, Carocok Tarusan, West Sumatra Province - Brown, Arthur; Ukhwatul, Vify (Jurnal Perikanan dan Kelautan, 2025)
Open-access fishery resources encourage fishing competition that can cause stock decreases and overfishing; therefore, bioeconomic management based on sustainability potential and utilization rate assessments is needed to maintain sustainability. This research aims to determine anchovies' potential and utilization rate (Stolephorus sp) at the UPTD Fishery Port Region I, Carocok Tarusan, West Sumatra Province. The research was conducted in December 2024 using secondary data in the form of annual catch and fishing effort for 2016-2023, obtained from relevant institutions. The methods used were the Catch Per Unit Effort (CPUE) and surplus production models of Schaefer and Fox. Based on the results of the analysis, the Schaefer surplus production model was the most appropriate model for analyzing the potential of anchovies at the Carocok Tarusan Fishing Port. This model estimates MSY at 445,211.65 kg/year with an optimum effort of 6,547 trips/year. JTB is estimated at 356,169.32 kg/year. During the research period, the average utilization rate of anchovies reached 54%, showing that fish stocks were in a moderate state. This means anchovy resources have not been overexploited and can still be utilized optimally. The exploitation rate of 33% indicates that there are still opportunities to increase fishing efforts while continuing to apply the principles of sustainable management.